Current collector and preparation method thereof, pole piece, secondary battery and electric device

The copper foil prepared by electroplating, combined with the linear oscillation current process, solves the problem of reduced mechanical strength of the secondary battery current collector during extremely thinning, and realizes a high energy density, safety and low cost secondary battery.

CN119852415APending Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411059645.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-02
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The mechanical strength of the existing secondary battery current collector is reduced during the extremely thinning process, which cannot meet the market's demand for high energy density, high safety and low-cost secondary batteries.

Method used

Electroplating copper foil with excellent mechanical properties was prepared by electroplating method. The yield strength ratio of the copper foil was between 0.55 and 0.75 and the elongation of the breaking was between 5.5% and 7.5%. The grain size and structure of the copper foil were controlled by linear oscillation current to improve its bending resistance.

Benefits of technology

It significantly improves the mechanical strength and plasticity of copper foil, reduces brittleness, improves deformation stability, reduces safety hazards of secondary batteries, and reduces manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852415A_ABST
    Figure CN119852415A_ABST
Patent Text Reader

Abstract

The invention provides a current collector and a preparation method thereof, a pole piece, a secondary battery and an electric device. The current collector comprises an electroplated copper foil, and under the test conditions that the temperature is 10-30 DEG C, the sample length * width is (50 + / -0.25 mm) * (15 + / -0.25 mm), and the stretching speed is 50 + / -0.5 mm / min, the yield ratio of the copper foil is 0.55-0.75, and the elongation at break is 5.5-7.5%. The current collector comprises the electroplated copper foil with good tensile property and extensibility, and the bending resistance of the copper foil is remarkably improved, so that the breakage of the copper foil in the pole piece winding process can be reduced or avoided, and the potential safety hazard of the secondary battery is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a current collector and a preparation method thereof, a pole piece, a secondary battery and an electrical device. Background Art

[0002] As secondary batteries are widely used in energy storage power systems such as hydropower, thermal, wind and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields, the market's requirements for high energy density, high safety and low cost of secondary batteries are constantly increasing. The trend of battery current collectors is to become extremely thin, which puts higher requirements on the mechanical properties of the current collectors.

[0003] When the thickness of the current collector is reduced, its mechanical strength will decrease, and it cannot meet the market demand for high energy density, high safety and low cost secondary batteries. Therefore, it is necessary to provide a current collector with good mechanical properties to meet the needs of the new generation of secondary batteries for extremely thin current collectors. Summary of the invention

[0004] The present application provides a current collector and a preparation method thereof, as well as a pole piece, a secondary battery and an electric device comprising the current collector. The current collector comprises an electroplated copper foil having good tensile and elongation properties, and the bending resistance of the copper foil is significantly improved, which can reduce or avoid the breakage of the copper foil during the winding process of the pole piece, thereby reducing the safety risks of the secondary battery.

[0005] In a first aspect, the present application provides a current collector, the current collector comprising an electroplated copper foil, under the test conditions of 10°C-30°C, sample length×width of (50±0.25mm)×(15±0.25mm), and tensile speed of 50±0.5mm / min, the yield strength ratio of the copper foil is 0.55-0.75 and the elongation at break is 5.5%-7.5%. The copper foil has good tensile strength and elongation at break, and exhibits excellent mechanical strength and plasticity.

[0006] In some embodiments, the yield strength ratio of the copper foil is 0.55-0.72, and / or the elongation at break is 5.5%-7.3%. The copper foil can further improve mechanical strength and plasticity, reduce brittleness, and improve deformation stability.

[0007] In some embodiments, the tensile strength of the copper foil is 500 MPa-650 MPa. In some embodiments, the tensile strength of the copper foil is 510 MPa-610 MPa. The tensile strength of the copper foil within the above range helps to improve the mechanical strength of the copper foil and can be applied to high energy density secondary batteries.

[0008] In some embodiments, the maximum and minimum grain sizes of the copper foil grains range from 2 μm to 4 μm. In some embodiments, the maximum and minimum grain sizes of the copper foil grains range from 2.3 μm to 3 μm.

[0009] The copper foil with the grain size distribution further increases the geometric necessary dislocation, increases the grain dislocation density, enhances the resistance to grain dislocation movement and the occurrence of concentrated stress during the copper foil deformation process, thereby improving the mechanical strength of the copper foil and the deformation stability.

[0010] In some embodiments, the copper foil satisfies at least one of the following conditions:

[0011] (1) The average grain size of copper foil is 0.2μm-0.7μm;

[0012] (2) The minimum grain size of copper foil is 0.1μm-0.3μm;

[0013] (3) The maximum grain size of copper foil is 2μm-4μm.

[0014] Grains of different sizes in copper foil have different work hardening capabilities due to different grain boundary densities, and thus exhibit different mechanical strengths and bending resistance. Different grain sizes in copper foil can enhance the work hardening differences of grains, enhance the ability to suppress strain localization, reduce the occurrence of concentrated stress, and reduce the brittleness of copper foil while improving the mechanical strength of copper foil. In addition, changes in the size of copper foil grains are conducive to inducing a higher density of geometric necessary dislocations, increasing the resistance to grain slip movement and improving the plasticity of copper foil, so that copper foil has both good deformation stability and bending resistance, and improves the safety and service life of secondary batteries.

[0015] In some embodiments, the copper foil has a thickness of 4 μm to 8 μm. The copper foil has a low thickness and light weight, which helps reduce the weight of the battery and further improve the energy density.

[0016] The second aspect of the present application provides a method for preparing a current collector, including preparing an electroplated copper foil by an electroplating method, wherein the electroplating method includes applying a linear oscillating current to an electrolyte to reduce and deposit copper ions in the electrolyte to form copper foil. Under the test conditions of 10°C-30°C, sample length×width of (50±0.25mm)×(15±0.25mm), and a tensile speed of 50±0.5mm / min, the yield strength ratio of the copper foil is 0.55-0.75 and the elongation at break is 5.5%-7.5%.

[0017] The preparation method has mature technology, low equipment requirements and low manufacturing cost. The prepared copper foil not only has excellent mechanical strength and good deformation stability, but also helps to reduce the manufacturing cost of secondary batteries.

[0018] In some embodiments, the linear oscillating current of the electroplating method varies in the range of 20KA-45KA.

[0019] In some embodiments, the variation period of the linear oscillating current in the electroplating method is 10ms-500ms.

[0020] The current size can control the deposition rate of copper ions, and the size of the grains in the copper foil can be adjusted by adjusting the current change range of the linear oscillating current. Grains of different sizes are conducive to improving the grain boundary density and geometric dislocation of the copper foil, improving the degradation of grain boundary tortuosity caused by the reduction of grain size, strengthening the strength of the copper foil and improving the bending resistance, and improving the brittle defects caused by fine grain strengthening. The current change cycle can adjust the particle size span of the maximum and minimum particle sizes in the copper foil, which is conducive to the full accumulation of geometric dislocations and the increase of the ability to suppress local strain of grains of different sizes, improving the mechanical strength of the copper foil while improving deformation stability.

[0021] In some embodiments, in the electroplating method, the distance between the cathode electrode and the anode electrode is 10 mm to 20 mm.

[0022] In some embodiments, the temperature of the electroplating deposition is 40°C-60°C.

[0023] In some embodiments, the electroplating deposition time is greater than or equal to 80 seconds.

[0024] Adjusting the electroplating parameters helps to prepare copper foil with regular grains and appropriate thickness, thereby improving the quality of copper foil.

[0025] In some embodiments, the electrolyte comprises:

[0026] a leveling agent, the leveling agent comprising collagen;

[0027] A wetting agent, wherein the wetting agent comprises one or more of polyethylene glycol and hydroxyethyl cellulose;

[0028] The brightener comprises sodium polydisulfide dipropane sulfonate.

[0029] In some embodiments, the brightener includes sodium poly(dipropylene glycol disulfide) sulfonate.

[0030] The leveler in the electrolyte can adhere to the tip of the copper foil with a fast deposition rate, inhibit grain growth, balance the growth rate of the pit and the tip, and improve the flatness of the copper foil. The wetting agent can improve the wettability of the electrolyte and the substrate. The wettability of the electrolyte on the cathode is sufficient to enable it to achieve rapid electrodeposition with a large current, increase the nucleation rate of the copper foil, and reduce the grain size in the copper foil. The brightener can make the grain size of the copper foil smaller, reduce the surface roughness of the copper foil, and improve the smoothness of the surface.

[0031] In some embodiments, the electrolyte comprises: collagen at a concentration of 10-300 mg / L, polyethylene glycol at a concentration of 20-100 mg / L, hydroxyethyl cellulose at a concentration of 10-100 mg / L, and sodium polydisulfide dipropane sulfonate at a concentration of 50-200 mg / L.

[0032] In some embodiments, the electrolyte comprises: collagen at a concentration of 90-120 mg / L, polyethylene glycol at a concentration of 20-80 mg / L, hydroxyethyl cellulose at a concentration of 10-80 mg / L, and sodium polydisulfide dipropane sulfonate at a concentration of 50-150 mg / L.

[0033] In some embodiments, the electrolyte includes chloride ions at a concentration of 10-100 mg / L and copper ions at a concentration of 60-100 g / L, which can further improve the electrodeposition process.

[0034] The preparation method is helpful to form a dense, flat copper foil with continuously changing grain size, which has excellent yield strength ratio and elongation at break, significantly improved tensile strength and bending resistance, good mechanical strength and deformation stability, and is beneficial to improving the safety performance of high energy density or high expansion batteries.

[0035] The third aspect of the present application provides a pole piece, comprising the current collector of the first aspect of the present application or the current collector prepared by the method of the second aspect. The current collector comprises a copper foil, the mechanical strength of the copper foil is improved, and the brittle defects of the copper foil deposited by direct current are reduced, the deformation stability of the copper foil is improved, and it can be applied to secondary batteries with high expansion force, which is conducive to further improving the energy density of the secondary battery.

[0036] A fourth aspect of the present application provides a secondary battery, comprising the electrode sheet according to the third aspect of the present application.

[0037] A fifth aspect of the present application provides an electrical device, comprising the secondary battery of the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 is a schematic diagram of a secondary battery according to an embodiment of the present application;

[0039] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown;

[0040] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application;

[0041] Figure 4 is a schematic diagram of a battery pack according to an embodiment of the present application;

[0042] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown;

[0043] Figure 6 is a schematic diagram of an electrical device using a secondary battery according to an embodiment of the present application as a power source;

[0044] Figure 7 A schematic diagram showing current changes in preparing copper foil according to an embodiment of the present application is shown;

[0045] Figure 8 The tensile curve of the copper foil of Example 1 of the present application is shown;

[0046] Fig. 9 The tensile curve of the copper foil of Example 2 of the present application is shown;

[0047] Fig.10 The tensile curve of the copper foil of Example 3 of the present application is shown;

[0048] Fig.11 The tensile curve of the copper foil of Example 4 of the present application is shown;

[0049] Fig.12 The tensile curve of the copper foil of Example 5 of the present application is shown;

[0050] Fig.13 The tensile curve of the copper foil of Comparative Example 1 of the present application is shown;

[0051] Fig.14 The inverse pole figure distribution diagram of the electron backscatter diffractometer (EBSD) of the copper foil of Example 1 of the present application is shown;

[0052] Fig.15 The particle size distribution diagram of the copper foil of Example 1 of the present application measured by electron backscatter diffractometer (EBSD) is shown;

[0053] Fig.16 The inverse pole figure distribution diagram of the electron backscatter diffractometer (EBSD) of the copper foil of Example 2 of the present application is shown;

[0054] Fig.17 The particle size distribution diagram of the copper foil of Example 2 of the present application measured by electron backscatter diffractometer (EBSD) is shown;

[0055] Fig.18 The inverse pole figure distribution diagram of the electron backscatter diffractometer (EBSD) of the copper foil of Comparative Example 1 of the present application is shown;

[0056] Fig.19 The particle size distribution diagram of the copper foil of Comparative Example 1 of the present application measured by electron backscatter diffractometer (EBSD) is shown.

[0057] Description of reference numerals:

[0058] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION

[0059] Below, the embodiments of the positive electrode active material and its manufacturing method, positive electrode sheet, secondary battery, battery module, battery pack and electrical device of the present application are specifically disclosed with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0060] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0061] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0062] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0063] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0064] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0065] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0066] Typically, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions (for example, lithium ions, sodium ions) are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting active ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, which mainly plays the role of preventing the positive and negative electrodes from short-circuiting, and at the same time allows active ions to pass through. The negative electrode sheet includes a negative current collector, which is used to restrain the expansion of the battery cell to prevent the anode from breaking during the cycle.

[0067] As the market demand for battery energy density increases, in order to reduce safety hazards, the mechanical strength requirements of secondary batteries for current collectors, especially negative current collectors, have also increased. In the prior art, the mechanical strength of the current collector is usually improved by refining the grains, increasing the grain boundary density and dislocation movement resistance. However, after the grains are refined, the tortuosity of the grain boundaries is reduced, and the current collector breaks along the grain under bending or force, resulting in high brittleness of the current collector, and the inner ring pole piece of the battery cell is very easy to break, causing safety hazards.

[0068] [current collector]

[0069] Based on this, the first aspect of the present application provides a current collector, the current collector includes an electroplated copper foil, under the test conditions of 10°C-30°C, sample length×width of (50±0.25mm)×(15±0.25mm), and tensile speed of 50±0.5mm / min, the yield strength ratio of the copper foil is 0.55-0.75 and the elongation at break is 5.5%-7.5%. When the yield strength ratio and the elongation at break are within the range, the current collector of the present application has both excellent mechanical strength and plasticity.

[0070] Herein, electroplated copper foil refers to copper foil prepared by electroplating. In the prior art, copper foil can also be prepared by calendering, and copper foil prepared by calendering is referred to as rolled copper foil in this article. Electroplated copper foil and rolled copper foil have different physical properties and grain structures. Specifically, the surface uniformity and flatness of rolled copper foil are better than those of electrolytic copper foil, but the purity is not as good as that of electrolytic copper foil. Rolled copper foil is basically transverse grains or mainly transverse grains, while electroplated copper foil has columnar grain structure. Electroplated copper foil and rolled copper foil can be easily distinguished by EBSD testing.

[0071] In this article, the term "yield strength ratio" refers to the ratio of yield strength to tensile strength, which can reflect the ability of copper foil to form a certain shape and maintain this shape after processing or stress, that is, formability.

[0072] In this article, the term "yield strength" refers to the yield limit of a material when yielding occurs. In order to measure the yield characteristics of a material, the stress value when permanent residual plastic deformation equals a certain value (generally 0.2% of the original length) is defined as the yield strength.

[0073] In this article, the term "tensile strength" refers to the maximum bearing strength of the specimen when the specimen is continuously loaded until it breaks, that is, the stress value of permanent residual plastic deformation.

[0074] The yield strength ratio refers to the ratio of the metal's yield strength to its tensile strength. The yield strength is the stress value at which the metal begins to produce plastic deformation during the stress process, and the tensile strength is the maximum stress value that the metal can withstand during the stretching process. The lower the yield strength ratio, the greater the plastic deformation that the metal can withstand after yielding, and the better the ductility and toughness. An increase in the yield strength ratio can reduce the strain hardening ability of the copper foil grains and reduce the copper foil's ability to resist lateral bending. A decrease in the yield strength ratio can enhance the strain hardening ability of the copper foil grains and improve the plasticity of the copper foil. Copper foil with a suitable yield strength ratio exhibits excellent mechanical strength and plasticity.

[0075] In this article, the term "elongation at break" refers to the ratio of the length change of a material from the time it undergoes plastic deformation until it breaks after being subjected to force to the original length. It is usually expressed as a percentage and is an important parameter for measuring the material's ability to deform under stress during stretching. Copper foil with a suitable elongation at break exhibits good plasticity.

[0076] In the present application, the yield strength, tensile strength and elongation at break of the copper foil can be tested by methods known in the art, such as testing according to the GB / T 5230-1995 "Electrolytic Copper Foil" standard. As an example, cut at least 4 specimens with a test area length of 50±0.25mm and a width of 15±0.25mm, and continuously load the specimens at a tensile speed of 50±0.5mm / min at room temperature (10℃-30℃) until they break, and the maximum load divided by the cross-sectional area of ​​the specimen is used as the tensile strength of the specimen. The cross-sectional area of ​​the specimen can be calculated by dividing the mass of the specimen by the product of the length and density of the specimen. The elongation at break can be calculated according to the displacement method after the above test. The test area refers to the detection area during instrument testing. Considering that the specimen may need to be fixed by a clamp during testing, the length and width of the specimen can be greater than the length and width of the test area.

[0077] In some embodiments, the yield strength ratio of the copper foil is 0.55-0.72, 0.55-0.70, 0.60-0.75. In some embodiments, the yield strength ratio of the copper foil is 0.55, 0.58, 0.60, 0.62, 0.65, 0.68, 0.70, 0.72, 0.75, the range between any two of the above values ​​or any value within the range.

[0078] In some embodiments, the elongation at break of the copper foil is 5.5%-7.3%, 5.5%-7.0%, 6.0%-7.5%, 6.0%-7.3%. In some embodiments, the elongation at break of the copper foil is 5.5%, 5.7%, 6.0%, 6.2%, 6.5%, 6.8%, 7.0%, 7.3%, 7.5%, the range between any two of the above values ​​or any value within the range.

[0079] In some embodiments, the yield strength ratio of the copper foil is 0.55-0.72 and the elongation at break is 5.5%-7.3%, which is beneficial for the copper foil to have both good mechanical properties and high plasticity.

[0080] In some embodiments, the tensile strength of the copper foil is 500MPa-650MPa, and can be 510MPa-610MPa. In some embodiments, the tensile strength of the copper foil is 500MPa, 550MPa, 580MPa, 600MPa, 620MPa, 650MPa, a range between any two of the above values, or any value within the range. The tensile strength within the range is beneficial for the copper foil to maintain good plasticity without excessively reducing the mechanical strength of the copper foil.

[0081] In some embodiments, the average grain size of the copper foil grains is 0.2 μm-0.7 μm, and can be 0.3 μm-0.6 μm, 0.3 μm-0.5 μm, 0.4 μm-0.6 μm, 0.4 μm-0.5 μm. In some embodiments, the average grain size of the copper foil grains is 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, 0.55 μm, 0.6 μm, 0.65 μm, 0.7 μm, the range between any two of the above values, or any value within the range.

[0082] In this paper, the average grain size of copper foil grains refers to the inverse pole figure distribution diagram obtained by the electron backscatter diffractometer (EBSD) test of the copper foil cross section. The grain size in the copper foil cross section is counted by the imageJ analysis software equipped with the Oxford C-Nano+ electron backscatter diffractometer to make a quantitative distribution diagram. The equivalent circular diameter of the grain is used as the grain size, and the average grain size is obtained by fitting with the skewed distribution.

[0083] In some embodiments, the minimum grain size of the copper foil grains is 0.1 μm-0.3 μm, and can be 0.1 μm-0.2 μm, 0.15 μm-0.25 μm, 0.2 μm-0.3 μm. In some embodiments, the minimum grain size of the copper foil grains is 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, the range between any two of the above values, or any value within the range.

[0084] In this article, the minimum grain size of copper foil refers to the grain size in the cross section of copper foil obtained by the electron backscatter diffractometer (EBSD) test. The imageJ analysis software of the Oxford C-Nano+ electron backscatter diffractometer is used to count the grain size in the cross section of copper foil, and the number distribution diagram is made. The equivalent circle diameter of the grain is used as the grain size, and the skewed distribution is used for fitting. In the statistical results, the smallest grain size is the minimum grain size of the copper foil.

[0085] In some embodiments, the maximum grain size of the copper foil grains is 2 μm-4 μm, and can be 2.3 μm-3.5 μm, 2 μm-3 μm, 2.5 μm-3.0 μm. In some embodiments, the maximum grain size of the copper foil grains is 2.0 μm, 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 3.0 μm, 3.2 μm, 3.4 μm, 3.6 μm, 3.8 μm, 4.0 μm, the range between any two of the above values, or any value within the range.

[0086] In this article, the maximum grain size of copper foil refers to the inverse pole figure distribution diagram obtained by the electron backscatter diffractometer (EBSD) test of the copper foil cross section. The imageJ analysis software supporting the Oxford C-Nano+ electron backscatter diffractometer is used to count the grain size in the copper foil cross section, and the number distribution diagram is made. The equivalent circle diameter of the grain is used as the grain size, and the skewed distribution is used for fitting. In the statistical results, the largest grain size is the maximum grain size of the copper foil grain.

[0087] The particle size span between the maximum particle size and the minimum particle size is the difference between the maximum particle size and the minimum particle size.

[0088] In some embodiments, the maximum and minimum grain sizes of the copper foil grains range from 2 μm to 4 μm, and may be 2 μm to 3.5 μm, 2.5 μm to 3.5 μm, or 2.5 μm to 3.0 μm. In some embodiments, the maximum and minimum grain sizes of the copper foil grains range from 2 μm to 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 3 μm, 3.2 μm, 3.4 μm, 3.6 μm, 3.8 μm, or 4.0 μm, or any range between any two of the above values ​​or any value within the range.

[0089] The appropriate grain size span can fully accumulate geometrically required dislocations, increase the grain dislocation density, increase the resistance to grain dislocation movement and the occurrence of concentrated stress during copper foil deformation, thereby strengthening the strength of copper foil and improving its brittleness; it can also enhance the collaborative sliding resistance of grains, increase the mechanical strength of copper foil and improve deformation stability, which can meet the use requirements of high energy density batteries or high expansion batteries and improve the safety of secondary batteries.

[0090] In copper foil, large-sized grains have higher mobility of grain dislocations and high plasticity, while small-sized grains increase the resistance to grain dislocation movement due to the increased grain boundary density, thereby improving the mechanical strength of copper foil. Therefore, metal materials with different grain sizes show obvious differences in work hardening. The change in the size of copper foil grains increases the difference in work hardening of grains, enhances the ability to suppress strain localization, reduces the occurrence of concentrated stress, and reduces the brittleness of copper foil while improving the mechanical strength of copper foil. In addition, it is also beneficial to induce a higher density of geometric necessary dislocations, increase the resistance to grain slip movement, and improve the plasticity of copper foil. This helps to prolong the elastic-plastic transition stage in the early stage of copper foil deformation, thereby obtaining higher additional strengthening and work hardening, improving the deformation stability of copper foil, and improving the safety and service life of secondary batteries.

[0091] The average particle size, maximum particle size, minimum particle size, and particle size span of the maximum particle size and the minimum particle size in the copper foil can be tested by methods known in the art. As an example, the cross section of the copper foil is measured by electron backscatter diffractometer (EBSD) and scanning electron microscope to obtain an inverse polar figure distribution map, and the particle size of the crystal grains in the cross section is counted by imageJ analysis software equipped with Oxford C-Nano+ electron backscatter diffractometer to make a quantity distribution map, such as Figure 14-17 As shown, the equivalent circular diameter of the grain is taken as the grain size, and the skewed distribution is used for fitting to obtain the average grain size, maximum grain size, and minimum grain size of the grains, and the grain size span of the maximum grain size and the minimum grain size is calculated.

[0092] In some embodiments, the thickness of the copper foil is 4 μm-8 μm. In some embodiments, the thickness H of the copper foil is 4.5 μm-8 μm, and can be 5 μm-8 μm. In some embodiments, the thickness H of the copper foil is 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, the range between any two of the above values, or any value within the range.

[0093] In this application, the thickness of the copper foil can be tested by a method known in the art. As an example, a 20×15 cm 2 The cut sample is placed on an electronic balance for weighing to obtain the sample weight. Then, according to the density of copper foil, ρ is 8.96 g / cm 3 Calculate the volume of the spline. Given the length and width of the spline, the thickness of the spline can be calculated.

[0094] The copper foil has low thickness and light weight, which helps to reduce the weight of the battery and further improve the energy density.

[0095] [Preparation method]

[0096] The second aspect of the present application provides a method for preparing a current collector, including preparing an electroplated copper foil by an electroplating method, wherein the electroplating method includes applying a linear oscillating current to an electrolyte to reduce and deposit copper ions in the electrolyte to form copper foil. Under the test conditions of 10°C-30°C, a sample length × width of (50±0.25mm) × (15±0.25mm), and a tensile speed of 50±0.5mm / min, the copper foil has a yield strength ratio of 0.55-0.75 and an elongation at break of 5.5%-7.5%.

[0097] In this article, the term "electroplating" refers to a method of depositing metal or alloy on the surface of a workpiece to form a metal layer by using the principle of electrolysis.

[0098] In this document, the term "linear oscillating current" refers to an oscillating current with a linear current waveform that changes linearly periodically.

[0099] Compared with the calendering method in the prior art, the electroplating process is mature and simple, has low equipment requirements and low manufacturing cost. The prepared copper foil not only has excellent mechanical strength and good deformation stability, but also helps to reduce the manufacturing cost of secondary batteries.

[0100] In the prior art, direct current is usually used to deposit copper in the process of preparing copper foil by electroplating. By adjusting the size of the direct current, copper foil with fine and uniform grains can be obtained to enhance the strength of the copper foil. However, this reduces the plasticity of the copper foil. Due to the reduced ability to suppress strain localization, the copper foil is prone to concentrated stress during deformation and has low bending resistance, which leads to the risk of brittle fracture. The preparation method provided in the present application uses a linear oscillating current, and the nucleus formation and growth of the reduced copper ions are controlled and adjusted by the size of the current, thereby adjusting the size of the grains and forming a copper foil with a heterogeneous structure, while strengthening the strength of the copper foil and maintaining excellent plasticity.

[0101] In some embodiments, the peak value of the linear oscillating current is 35KA-45KA, and can be 40KA-45KA. In some embodiments, the peak value of the linear oscillating current is 35KA, 38KA, 39KA, 40KA, 43KA, 45KA, the range between any two of the above values, or any value between the ranges.

[0102] In some embodiments, the valley value of the linear oscillating current is 15KA-25KA, and can be 20KA-25KA. In some embodiments, the valley value of the linear oscillating current is 15KA, 18KA, 19KA, 20KA, 23KA, 35KA, a range between any two of the above values, or any value between the ranges.

[0103] In some embodiments, the variation range of the linear oscillating current is 20KA-45KA, and can be optionally 20KA-40KA.

[0104] In some embodiments, the variation period of the linear oscillating current is 10ms-500ms, and may be 20ms-50ms, 50ms-100ms. In some embodiments, the variation period of the linear oscillating current is 20ms, 30ms, 40ms, 50ms, 60ms, 70ms, 80ms, 100ms, 150ms, 200ms, 250ms, 300ms, 350ms, 400ms, 450ms, 500ms, or any range between any two of the above values ​​or any value between the ranges.

[0105] In this article, the term "peak value" refers to the maximum current value of the linear oscillating current, usually the value at the peak of the linear current waveform. Similarly, the term "valley value" refers to the minimum current value of the linear oscillating current, usually the value at the valley of the linear current waveform.

[0106] In this article, the term "variation period" refers to the time between two adjacent peaks or troughs in a linear current waveform, and the unit is ms.

[0107] During the copper ion deposition process, increasing the current can speed up the deposition rate of copper ions, thus forming fine copper grains; reducing the current can reduce the deposition rate of copper ions, which helps to form regular and orderly large-sized grains. Through the continuous change of the linear oscillating current, the size of the copper grains formed by the deposition changes.

[0108] In addition, adjusting the peak value is conducive to controlling the average particle size of fine grains, improving the degradation of grain boundary tortuosity caused by particle size reduction, improving brittleness while strengthening fine grains, and improving the bending resistance of copper foil. Adjusting the current valley value can control the average particle size of large grains in copper foil, reduce or avoid the weakening of strength and excessive plasticity of large-sized grains due to increased particle size. Adjusting the variation period of sinusoidal current helps to adjust the particle size span of the maximum and minimum particle sizes in copper foil, so that large and small grains have sufficient particle size distribution, thereby accumulating more geometrically required dislocations and differences in work hardening ability, improving dislocation movement and grain cooperative sliding resistance, and increasing the ability to suppress local strain, so that copper foil improves mechanical strength while improving brittleness.

[0109] In some embodiments, Figure 7 As shown, the variation range of the linear oscillating current is 20KA-45KA, and the variation period is 50ms.

[0110] In some embodiments, the preparation method is a continuous production method.

[0111] In some embodiments, the preparation method is a roller deposition method. Its working principle is that the cathode roller is connected to the negative electrode of the power supply, and the anode tank is connected to the positive electrode of the power supply. When the electrolyte containing copper ions enters the anode tank, an electric field is formed between the positive and negative electrodes. Under the action of the electric field, the copper ions migrate and deposit on the surface of the cathode roller, and the deposited copper foil is peeled off from the cathode roller and rolled on another roller. The electrolyte is continuously added and circulated, and the copper ions are continuously deposited on the cathode roller under the action of the electric field, continuously peeled off and rolled on the winding shaft. This preparation method can realize the continuous production of large-scale copper foil, providing the possibility for industrial application.

[0112] In some embodiments, the cathode electrode is a titanium roller or plate.

[0113] In some embodiments, the anode electrode is a titanium substrate plate, such as a DSA (Dimensionally Stable Anode) coated titanium anode (iridium series).

[0114] In some embodiments, the spacing between the cathode electrode and the anode electrode is 10 mm to 20 mm. In some embodiments, the spacing between the cathode electrode and the anode electrode is 15 mm, 16 mm, 17 mm, 18 mm, 19 mm, 20 mm, the range between any two of the above values ​​or any value between the ranges.

[0115] In some embodiments, the temperature of the electroplating deposition is 45° C.-60° C. In some embodiments, the deposition temperature can be 45° C., 50° C., 55° C., 60° C., a range between any two of the above values, or any value in the range.

[0116] In some embodiments, the electroplating deposition time is greater than or equal to 80 seconds, and can be 80 seconds to 300 seconds. In some embodiments, the deposition time can be 80 seconds, 100 seconds, 200 seconds, 220 seconds, 240 seconds, 280 seconds, 300 seconds, 400 seconds, 500 seconds, 800 seconds, 1000 seconds, the range between any two of the above values, or any value within the range.

[0117] In some embodiments, the electrolyte includes: a leveling agent including collagen; a wetting agent including one or more of polyethylene glycol and hydroxyethyl cellulose; and a brightening agent including sodium polydisulfide dipropane sulfonate.

[0118] In this article, the term "leveler" refers to a substance added to the electrolyte to improve the flatness of the coating. It can adhere to the tip of the copper foil with a fast deposition rate, inhibit grain growth, balance the growth rate of pits and tips, and improve the flatness of the copper foil.

[0119] In this article, the term "wetting agent" refers to a substance used to reduce the interfacial tension between the electrolyte / electrode and to make the coating adhere better to the substrate. The wetting agent can improve the wettability of the electrolyte and the substrate. The wettability of the electrolyte on the cathode is sufficient to enable rapid electrodeposition with a large current, increase the nucleation rate of the copper foil, and reduce the grain size in the copper foil.

[0120] In this article, the term "brightener" refers to a substance that improves the smoothness of the coating and reduces the surface roughness. Brightener can make the grain size of copper foil smaller, reduce the surface roughness of copper foil, and improve the smoothness of the surface.

[0121] In some embodiments, the electrolyte includes 10-300 parts by weight of a leveler, 20-200 parts by weight of a wetting agent, and 50-200 parts by weight of a brightener.

[0122] Furthermore, the electrolyte also includes 60-100 parts by weight of copper ions (calculated by copper atomic mass) and 10-100 parts by weight of chloride ions (calculated by chlorine atomic mass). Furthermore, the electrolyte also includes 60-110 parts by weight of sulfuric acid.

[0123] In the electrolyte, copper ions provide copper sources for the formation of copper foil. Chloride ions can be used in combination with wetting agents to further improve the electrodeposition process. Sulfuric acid can not only dissolve copper materials, but also maintain an acidic environment for the electrolyte to facilitate the reduction of copper ions.

[0124] In some embodiments, the concentration of the collagen in the electrolyte is 10-300 mg / L, and can be 90-120 mg / L. In some embodiments, the concentration of the collagen in the electrolyte is 10 mg / L, 30 mg / L, 50 mg / L, 80 mg / L, 100 mg / L, 120 mg / L, 150 mg / L, 180 mg / L, 200 mg / L, 300 mg / L, the range between any two of the above values, or any value within the range.

[0125] In some embodiments, the wetting agent includes hydroxyethylcellulose and polyethylene glycol.

[0126] In some embodiments, the concentration of the polyethylene glycol in the electrolyte is 10-200 mg / L, and can be 20-80 mg / L. In some embodiments, the concentration of the polyethylene glycol in the electrolyte is 10 mg / L, 20 mg / L, 30 mg / L, 40 mg / L, 50 mg / L, 60 mg / L, 70 mg / L, 80 mg / L, 100 mg / L, 150 mg / L, 200 mg / L, the range between any two of the above values, or any value between the ranges.

[0127] In some embodiments, the concentration of the hydroxyethyl cellulose in the electrolyte is 10-100 mg / L, optionally 10-80 mg / L. In some embodiments, the concentration of the hydroxyethyl cellulose in the electrolyte is 10 mg / L, 20 mg / L, 30 mg / L, 40 mg / L, 50 mg / L, 60 mg / L, 70 mg / L, 80 mg / L, 90 mg / L, 100 mg / L, the range between any two of the above values ​​or any value between the ranges.

[0128] In some embodiments, the concentration of the sodium polydisulfide propane sulfonate in the electrolyte is 50-200 mg / L, and can be 50-150 mg / L. In some embodiments, the concentration of the sodium polydisulfide propane sulfonate in the electrolyte is 50 mg / L, 80 mg / L, 90 mg / L, 100 mg / L, 110 mg / L, 120 mg / L, 150 mg / L, 180 mg / L, 200 mg / L, the range between any two of the above values, or any value between the ranges.

[0129] Sodium poly(disulfide-bis(propylene sulfonate)) is adsorbed on the cathode copper surface through the thiol functional group. The terminal sulfonate anions capture the hydrated copper ions in the electrolyte, thereby destroying their hydration, and interact with the chloride ions adsorbed on the cathode surface, so that electrons are transferred to the captured copper ions through the chloride ions, thereby greatly improving the electrochemical reduction rate of copper ions, refining the grains and achieving material strengthening.

[0130] In some embodiments, the electrolyte comprises: collagen at a concentration of 10-300 mg / L, polyethylene glycol at a concentration of 20-100 mg / L, hydroxyethyl cellulose at a concentration of 10-100 mg / L, and sodium polydisulfide dipropane sulfonate at a concentration of 50-200 mg / L.

[0131] In some embodiments, the electrolyte comprises: collagen at a concentration of 90-120 mg / L, polyethylene glycol at a concentration of 20-80 mg / L, hydroxyethyl cellulose at a concentration of 10-80 mg / L, and sodium polydisulfide dipropane sulfonate at a concentration of 50-150 mg / L.

[0132] In some embodiments, the electrolyte comprises chloride ions (calculated as chlorine atoms) at a concentration of 10-100 mg / L, and optionally, the chloride ion concentration is 20-80 mg / L.

[0133] In some embodiments, the electrolyte comprises sulfuric acid at a concentration of 60-110 g / L, optionally, sulfuric acid at a concentration of 80-100 g / L.

[0134] In some embodiments, the electrolyte comprises copper ions at a concentration of 60-100 g / L, optionally, at a concentration of 60-90 g / L.

[0135] In some embodiments, the electrolyte includes: 10-300 mg / L collagen, 20-100 mg / L polyethylene glycol, 50-200 mg / L sodium polydisulfide dipropane sulfonate, 10-100 mg / L chloride ions, 60-100 g / L copper ions, and 60-110 g / L sulfuric acid.

[0136] In some embodiments, the electrolyte includes: collagen at a concentration of 90-120 mg / L, polyethylene glycol at a concentration of 20-80 mg / L, sodium polydisulfide dipropane sulfonate at a concentration of 50-150 mg / L, chloride ions at a concentration of 20-80 mg / L, copper ions at a concentration of 60-90 g / L, and sulfuric acid at a concentration of 80-100 g / L.

[0137] In the method provided by the present application, the synergistic effect of the electrolyte and the electroplating parameters helps to form a dense, flat copper foil with continuously changing grain size, which has excellent yield strength ratio and elongation at break, significantly improved tensile strength and bending resistance, good mechanical strength and deformation stability, and is conducive to improving the safety performance of high energy density or high expansion batteries. At the same time, the preparation method can achieve large-scale manufacturing and has the prospect of industrial application.

[0138] [Negative electrode]

[0139] As an example of a negative electrode sheet, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0140] In some embodiments, the negative electrode current collector may be the current collector described in the first aspect of the present application, thereby providing a material basis for improving the energy density of the secondary battery and helping to improve the safety of the secondary battery.

[0141] In some embodiments, the negative electrode active material includes one of artificial graphite, natural graphite, soft carbon, hard carbon and mesophase carbon microbeads. In some embodiments, the negative electrode active material includes artificial graphite.

[0142] In some embodiments, the negative electrode film layer may further include other negative electrode active materials in addition to the above-mentioned graphite materials. In some embodiments, the other negative electrode active materials include but are not limited to one or more of conventional natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate. The silicon-based material may include one or more of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite and silicon alloy material. The tin-based material may include one or more of elemental tin, tin oxide and tin alloy material.

[0143] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0144] In some embodiments, the negative electrode plate further includes a conductive agent, which includes one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0145] In some embodiments, the conductive agent includes carbon black. In some embodiments, the conductive agent includes carbon nanotubes. In some embodiments, the conductive agent includes carbon black and carbon nanotubes. The conductive agent has a wide range of sources and excellent conductivity, which is beneficial to controlling the preparation cost of the secondary battery and improving the conductivity of the negative electrode sheet.

[0146] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0147] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0148] [Positive electrode]

[0149] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes a positive electrode active material.

[0150] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0151] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0152] In some embodiments, the positive electrode active material may adopt a positive electrode active material for a battery that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0153] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0154] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0155] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0156] [Electrolytes]

[0157] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0158] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0159] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0160] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0161] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0162] [Isolation film]

[0163] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0164] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0165] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0166] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0167] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0168] In addition, the secondary battery, battery module, battery pack, and electric device of the present application will be described below with reference to the drawings as appropriate.

[0169] In one embodiment of the present application, a secondary battery is provided.

[0170] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.

[0171] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0172] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0173] Figure 34 is an example of a battery module. Figure 3 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0174] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0175] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0176] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0177] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0178] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.

[0179] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.

[0180] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be light and thin, and a secondary battery may be used as a power source.

[0181] Example

[0182] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0183] Example 1

[0184] Preparation of copper foil

[0185] A copper plate or copper wire with a purity of more than 99.9% is dissolved in sulfuric acid with a mass content of 98% to obtain a copper sulfate solution, which is used as a copper source, and an electrolyte is prepared by adding additives and hydrochloric acid at 60°C. The pH of the prepared electrolyte is 3.5, wherein the concentration of collagen is 90 mg / L, the concentration of polyethylene glycol is 50 mg / L, the concentration of hydroxyethyl cellulose is 30 mg / L, the concentration of chloride ions is 30 mg / L, the concentration of sodium polydisulfide dipropane sulfonate is 75 mg / L, the concentration of copper ions is 90 g / L, the concentration of sulfuric acid is 100 g / L, and the rest is deionized water.

[0186] A linear current waveform is used to periodically apply current to the polished cathode titanium roller. The anode electrode is a titanium substrate plate. The area of ​​the titanium roller in the electrolyte is 0.3dm 2 The rotation speed of the titanium roller is 2m / min, the current is applied, the minimum current is 20KA, the maximum current is 45KA, the cycle is 50ms, the distance between the cathode and the anode is 20mm, and the deposition temperature is 60°C. The electroplating time is 224s, and the copper foil is deposited on the titanium roller with a thickness of 6μm.

[0187] Example 2-Example 5

[0188] The preparation process of Example 2 to Example 5 is basically similar to that of Example 1, but the minimum current is adjusted to 25KA, 30KA, 35KA, and 40KA, respectively.

[0189] Comparative Example 1

[0190] The preparation process of Comparative Example 1 is substantially similar to that of Example 1, but a direct current of 45KA is used to prepare the copper foil.

[0191] Performance Testing

[0192] (1) Mechanical properties test

[0193] According to GB / T 5230-1995 "Electrolytic Copper Foil", the strips were cut into 50 mm long L0 and 15 mm wide tensile strips at room temperature (10°C-30°C). The tensile properties were tested at 25°C using a universal testing machine, with the tensile rate set to 50 mm / min.

[0194] The cross-sectional area of ​​the stretched spline is Where ρ is 8.96 g / cm 3 , m is in grams, and L0 is in centimeters.

[0195] The sample is continuously loaded until it breaks (permanent residual plastic deformation is produced), and the maximum load F is read from the force gauge or tensile curve, and the formula is used to calculate the maximum load F. Calculate the tensile strength σ b .

[0196] Yield strength σ 0.2 The stress at which permanent residual plastic deformation is equal to 0.2% of the original length.

[0197] Yield strength ratio is yield strength σ 0.2 and tensile strength σ b ratio.

[0198] The distance between the two lines after the sample is broken is L1, which can be measured on the sample or read from the tensile curve. L1 can be measured by the straight line method or the displacement method according to the formula Calculate the elongation at break ε.

[0199] (2) Brittleness test

[0200] The copper foil was cut into test strips with a width of 15 mm. After being folded in half, it was rolled over with a 2 kg roller, then folded over and rolled again until a light-transmitting point appeared on the copper foil under a 2000 lux lamp. The number of folds was recorded.

[0201] (3) Grain characteristic test of copper foil

[0202] Electron backscatter diffraction (EBSD) combined with scanning electron microscopy was used to observe the cross section of the copper foil, where the electron backscatter diffractometer model was Oxford C-Nano+, and the inverse polar figure distribution map was obtained. The imageJ analysis software supporting the Oxford C-Nano+ electron backscatter diffractometer was used to count the equivalent circular diameter of the grains, and the average particle size, maximum particle size, minimum particle size, and the particle size span between the maximum and minimum particle sizes were determined.

[0203] The test results of the mechanical characteristics of the copper foils prepared in Examples 1-5 and Comparative Example 1 are shown in Table 1:

[0204] Table 1

[0205]

[0206] By Examples 1-5 and Figure 8-Figure 12 From the tensile curve, it can be seen that the linear current changes in the range of 20KA-45KA, the yield strength ratio of the prepared copper foil is in the range of 0.55-0.75, and the elongation at break is in the range of 5.5%-7.5%. The copper foil has both excellent yield strength ratio and elongation at break. The copper foil has good mechanical strength and plasticity, which significantly increases the number of times the copper foil can be folded.

[0207] Meanwhile, the tensile strength of the copper foil prepared in Examples 1-5 is in the range of 518 MPa-603 MPa, and the yield strength is in the range of 282 MPa-436 MPa, indicating that the copper foil has good mechanical strength and plasticity.

[0208] From Examples 1-5 and Comparative Example 1, Fig.13 In comparison, the tensile strength and yield strength ratio of the copper foil prepared under the condition of 45KA DC current are close to those of the copper foil prepared under the condition of linear oscillating current (20KA-40KA), but the elongation at break and the number of folding times are significantly worse, and the brittle defect of the copper foil is serious. Compared with the copper foil prepared by DC current deposition, the copper foil prepared by linear oscillating current deposition also improves the brittle defect of the copper foil under high tensile strength, significantly improves the anti-bending performance, and has better plasticity and deformation stability.

[0209] The test results of the grain characteristics of the copper foils of Examples 1-2 and Comparative Example 1 are shown in Table 2:

[0210] Table 2

[0211]

[0212] Figure 14-15 The cross-sectional electron backscatter diffractometer (EBSD) spectrum and particle size distribution diagram of the copper foil prepared in Example 1 are shown. Figure 16-Figure 17 The cross-sectional electron backscatter diffractometer (EBSD) spectrum and particle size distribution diagram of the copper foil prepared in Example 2 are shown. Figure 18-19 The cross-sectional electron backscatter diffractometer (EBSD) spectrum and particle size distribution diagram of the copper foil prepared in Comparative Example 1 are shown. It can be seen from the above figures and Table 2 that the particle size span of the grains in the copper foil prepared in Examples 1 and 2 is significantly higher than that of Comparative Example 1, which improves the ability of the copper foil to enhance the suppression of strain localization, reduces the occurrence of concentrated stress, improves the resistance to grain sliding, and reduces the brittleness of the copper foil while improving the mechanical strength of the copper foil. The copper foil has excellent plasticity. This also corresponds to the test results of the number of folding times of the copper foil. The number of folding times of the copper foil of Example 1 is significantly better than the number of folding times of the copper foil of Comparative Example 1.

[0213] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A current collector, characterized in that: The current collector includes electroplated copper foil. Under the test conditions of 10°C-30°C, sample length×width of (50±0.25mm)×(15±0.25mm), and tensile speed of 50±0.5mm / min, the yield strength ratio of the copper foil is 0.55-0.75 and the elongation at break is 5.5%-7.5%.

2. The current collector according to claim 1, characterized in that: The copper foil has a yield strength ratio of 0.55-0.72, and / or an elongation at break of 5.5%-7.3%.

3. The current collector according to claim 1 or 2, characterized in that: The tensile strength of the copper foil is 500MPa-650MPa.

4. The current collector according to any one of claims 1 to 3, characterized in that The tensile strength of the copper foil is 510MPa-610MPa.

5. The current collector according to any one of claims 1 to 4, characterized in that: The maximum and minimum grain sizes of the copper foil grains range from 2 μm to 4 μm.

6. The current collector according to any one of claims 1 to 5, characterized in that: The maximum and minimum grain sizes of the copper foil grains range from 2.3 μm to 3 μm.

7. The current collector according to any one of claims 1 to 6, characterized in that: The copper foil satisfies at least one of the following conditions: (1) The average grain size of copper foil is 0.2μm-0.7μm; (2) The minimum grain size of copper foil is 0.1μm-0.3μm; (3) The maximum grain size of copper foil is 2μm-4μm.

8. The current collector according to any one of claims 1 to 7, characterized in that: The copper foil has a thickness of 4 μm-8 μm.

9. A method for preparing a current collector, characterized in that: The invention comprises an electroplating method for preparing electroplated copper foil, wherein the electroplating method comprises applying a linear oscillating current to an electrolyte to reduce and deposit copper ions in the electrolyte to form copper foil. Under the test conditions of 10° C.-30° C., sample length×width of (50±0.25 mm)×(15±0.25 mm), and a tensile speed of 50±0.5 mm / min, the yield strength ratio of the copper foil is 0.55-0.75 and the elongation at break is 5.5%-7.5%.

10. The preparation method according to claim 9, characterized in that: The electroplating method satisfies one or more of the following conditions: (1) The variation range of the linear oscillating current is 20KA-45KA; (2) The variation period of the linear oscillating current is 10ms-500ms; (3) The distance between the cathode electrode and the anode electrode is 10 mm to 20 mm; (4) The temperature of electroplating deposition is 40°C-60°C; (5) The electroplating deposition time is greater than or equal to 80s.

11. The preparation method according to claim 9 or 10, characterized in that: The electrolyte comprises: a leveling agent, the leveling agent comprising collagen; A wetting agent, wherein the wetting agent comprises one or more of polyethylene glycol and hydroxyethyl cellulose; The brightener comprises sodium polydipropylene sulfonate.

12. The preparation method according to claim 11, characterized in that: The electrolyte comprises: collagen with a concentration of 10-300 mg / L, polyethylene glycol with a concentration of 20-100 mg / L, hydroxyethyl cellulose with a concentration of 10-100 mg / L, and sodium polydisulfide dipropane sulfonate with a concentration of 50-200 mg / L.

13. The preparation method according to any one of claims 9 to 12, characterized in that: The electrolyte comprises: collagen with a concentration of 90-120 mg / L, polyethylene glycol with a concentration of 20-80 mg / L, hydroxyethyl cellulose with a concentration of 10-80 mg / L, and sodium polydisulfide dipropane sulfonate with a concentration of 50-150 mg / L.

14. The preparation method according to any one of claims 9 to 13, characterized in that: The electrolyte includes chloride ions at a concentration of 10-100 mg / L and copper ions at a concentration of 60-100 g / L.

15. A pole piece, characterized in that: A current collector comprising the current collector described in any one of claims 1 to 8 or a current collector prepared by the preparation method described in any one of claims 9 to 14.

16. A secondary battery, characterized in that: Including the pole piece as described in claim 15.

17. An electrical device, characterized in that: Includes the secondary battery as claimed in claim 16.

Citation Information

Patent Citations

  • Electrolytic copper foil

    JP2014037582A

  • Electrolytic copper foil and process for producing same

    WO2014119355A1

  • Copper foil, preparation method therefor and use thereof

    WO2024124374A1

Cited By

  • Current collector and preparation method therefor, electrode sheet, secondary battery, and electric device

    WO2026026277A1